Maternal employment and childhood obesity: A European perspective - Wencke Gwozdz; Alfonso Sousa-Poza; Lucia A. Reisch; Wolfgang Ahrens; Stefaan De Henauw; Gabriele Eiben; Juan M. Fernandez-Alvira; Charalampos Hadjigeorgiou; Eva Kovacs; Fabio Lauria; Toomas Veidebaum; Garrath Williams; et al. (Universität Hohenheim, Forschungszentrum Innovation und Dienstleistung (FZID), 2013)
The substantial increase in female employment rates in Europe over the past two decades has often been linked in political and public rhetoric to negative effects on child development, including obesity. We analyse this association between maternal employment and childhood obesity using rich objective reports of various anthropometric and other measures of fatness from the IDEFICS study of children aged 2-9 in 16 regions of eight European countries. Based on such data as accelerometer measures and information from nutritional diaries, we also investigate the effects of maternal employment on obesity's main drivers: calorie intake and physical activity. Our analysis provides little evidence for any association between maternal employment and childhood obesity, diet or physical activity.
urn:nbn:de:bsz:100-opus-8504
Keywords: I12; J13; J22; 330; Maternal employment; Children; Obesity; Europe